Multigravida Hamil 30 Minggu dengan Partus Prematurus Imminens dan Pemendekan Serviks Janin Tunggal Hidup Presentasi Kepala : Laporan Kasus - Kurniaji, Inna; Zulfadli, Zulfadli (Medula, 2024)
Imminent preterm in the presence of a threat in pregnancy with emergence signs in 20 weeks – 37 weeks. Cervical shortening is one of the the common reason of preterm labour. Both Preterm labour and cervical shortening are are considered multifactorial syndromes. A short cervix is defined as a cervical length (CL) ≤25 mm on transvaginal sonography (TVS) before 24 weeks to 32 weeks of gestation.This is a case report. A 31 years old woman with preterm pregnancy come with pain that intermitently radiating to the waist and become worst seven hour before entering hospital. Complaints accompanied by blood and mucus discharge from the genitals. From physical examination found that moderate sick in general condition, compos mentis, Blood pressure 121/86 mmHg, heart rate 112x/min, respiratory rate 20x/min, temperature 36.5 C. General examination within normal limits. In obstetric examination found that fundus uteri is 3 finger under proccesus xiphoideus (25cm), his (+) 3x in 10 minutes duration 30-40 second, fetal heart rate 156x/min. In inspekulo examination found that portio is livide, OUE closed, not found active bleeding, erosion/laserasion/polip (-) and vaginal toucher not performed in this patient. In Transvaginal USG found cervical length 2.48 cm. The diagnosis are G5P3A1 in 30 weeks with imminent preterm and cervical shortening. Patient planned conservative therapy such as observation of his, fetal heart rate, and vital signs mother, IVFD ringer laktat + 2 amp isosuprine gtt xx/min, dexamethasone 2x10 mg, nifedipine 4x10 mg.